'Data must fall': mobile data pricing, regulatory paralysis and citizen action in South Africa. Issue 3 (17th February 2021) - Moyo, Dumisani; Munoriyarwa, Allen
ABSTRACT: South Africa's mobile telecommunications industry boasts four major players, namely Vodacom, MTN, CELL C and Telkom. On the face of it, this suggests a diverse market with healthy competition. However, the costs of mobile services, including data and voice calls remains among the highest in the world, suggesting a distorted and uncompetitive market. Despite increasing awareness of this reality, and growing public outcry, change has been slow and piecemeal, with both policymakers and regulatory authorities not taking decisive action. Using institutional policy analysis, document analysis and interviews with sampled actors from the telecommunication industry, civic society and the regulatory authority, this paper argues that a combination of regulatory paralysis, collusive behaviour by oligopolistic operators, indecisive government policy, and to some degree citizen inaction have led to sustained overpricing of mobile data in South Africa. It highlights the corporate dominance in the policing of this sector, which has implications for citizens' capacity to participate in various spheres of life, and hence for democracy. The paper is premised on the public interest theory and theories of universal (internet) access which are germane to understanding access to information as a human rights issue.